ANALYSIS OF WORKING CAPITAL MANAGEMENT AT SMALL-MEDIUM SCALEINDUSTRY IN DONDO SUB DISTRICT OF TOLITOLI DISTRICT - Nova Susanti; Asriani Hasanuddin; Max Nuralam (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
This study was conducted to determine the level of effectiveness of the working capital management and the level of profitability produced by small-medium scale industry (SMI) ofTovicoSejahtera in Dondo subdistrict of Tolitoli district.  The object of this study was the financial statements of the period 2015-2016 which covered items in the Balance Sheet report and Income statement. Data collection methods used in this research were documentation and interview. The analysis used was quantitative including activity ratio (working capital turnover, inventory turnover, Account Receivable Turnover) and profitability ratio (gross profit margin, net profit margin, ROI, ROE). The analysis shows that the ratio of working capital turnover, inventory turnover ratio and ROE ratio decreased in 2016 indicating that the performance of management decreased as well..But the overall working capital management at SMITovico Sejahterawas good in which the ratio of activity and profitability generated was above the general standard or above the average of the industry.  This result suggests thatSMITovico Sejahterais able to utilize and to manage its working capital effectively in generating high profit. Keywords: Effectiveness, profitability, and working capital management.